1323 VOLUNTEER-LED ONLINE GROUP EXERCISE FOR OLDER ADULTS: A FEASIBILITY AND ACCEPTABILITY STUDY. (16th January 2023) - Lim, S; Meredith, S; Agnew, S; Clift, E; Ibrahim, K; Roberts, H C
Abstract: Introduction: The health benefits of physical activity for older people are well recognised and include reduction in falls, improvement in frailty status and physical function. Nonetheless, physical inactivity remains a significant problem among older adults. This study aimed to determine the feasibility and acceptability of implementing online volunteer-led group exercise for community-dwelling older adults. Methods: This pre-post mixed methods study was conducted among older adults attending community social clubs. Eligible participants were aged ≥ 65 years, able to walk independently, and able to provide written consent. The intervention consisted of a once weekly volunteer-led online group chair-based exercise. The primary outcomes were the feasibility and acceptability of the intervention. Secondary outcomes included physical activity levels measured using the Community Health Model Activities Program for Seniors (CHAMPS) questionnaire, functional status (Barthel Index), and health-related quality of life (EQ-5D-5L). Outcomes were measured at baseline and at 6 months. Trials registration: NCT04672200. Results: Nineteen volunteers were recruited, 15 completed training and 9 were retained (mean age 68 years, 7 female). Thirty participants (mean age 77 years, 27 female) received the intervention and attended 54% (IQR 37-67) of exercise sessions. One minor adverse event was reported. Participants had no significant changes in secondary outcome measures, with a trend towards improvement in physical activity levels. The intervention was acceptable to volunteers, participants, and staff. The seated exercises were perceived as safe, manageable and enjoyable. Volunteers were relatable role models providing positive vicarious experiences that improved participants confidence to exercise within a friendly, non-judgmental environment. Technological issues, or reluctance to learn how to use technology were barriers to the intervention. The social interactions and sense of belonging motivated participation. Conclusions: Trained volunteers can safely deliver online group exercise for community-dwelling older adults and the intervention was feasible and acceptable to older adults, volunteers and club staff.